Estimation of water stress in maize hybrid PMH-13 from stress degree days measurements - Sakshi; Kalsi, Amandeep Kaur; Kumar, Rajeev (Journal of Scientific Agriculture, 2025)
A split-plot field experiment was performed to estimate water stress in maize cultivar PMH-13 which was grown using two different nitrogen levels: N1=150 kg ha-1 and N2=120 kg ha-1, each having four irrigation treatments based on IW/CPE ratios of 2.0 (I1), 1.5 (I2), 1.2 (I3) and 1.0 (I4), respectively. In the present study, three replications for each treatment have been employed to examine the impact of various irrigation treatments and nitrogen application on crop stress and yield. Among the four irrigation treatments, I4 exhibited the highest SDD, whereas I2 had the lowest value. Higher frequency of irrigation in I1 and I2 resulted in a reduction of crop stress due to the maintenance of higher soil moisture. Nitrogen application increased yield and reduced SDD. Thus, the irrigation strategy with IW/CPE ratio of 2.0 with nitrogen application of 150 kg ha-1 is observed to be most appropriate to reduce stress and maximize the yield of PMH-13.